Towards a heritage management strategy for Ras al-Khaimah (UAE) - Hilal, Ahmed; Kennet, Derek; Humble, Liz (Proceedings of the Seminar for Arabian Studies, 2015)
This paper reviews the work of the Department of Antiquities and Museums of Ras al-Khaimah and the challenges it currently faces. In relation to current norms and standards of international practice, the paper argues that the Department is doing much good work in the face of rapid development and that it needs to develop a long-term strategy to help it guide its work in future years. It argues that the strategy will need to be informed by international standards and developed in consultation with a wide range of groups and administrative departments within Ras al-Khaimah in order to be most effective.